Chemiluminescence of Oleic Acid Capped Black Phosphorus Quantum Dots for Highly Selective Detection of Sulfite in PM2.5 - Liu, Houjing; Su, Yingying; Deng, Dongyan; Song, Hongjie; Lv, Yi (Analytical chemistry (Washington), 2019)
Quantum dots (QDs), especially metal-free QDs with their unique optoelectronic properties, environmental friendliness, and excellent biocompatibility, have opened a new avenue to explore novel chemiluminescence (CL) systems for analytical applications. However, the unknown CL properties, relatively weak emission, and instability of some of them in water (e.g., black phosphorus QDs) often seriously hinder their further practical applications. Chemical modification trends have offered new properties for materials and have been proved to be desirable ways to establish sensing platforms with improved sensitivity and stability. Herein, oleic acid capped black phosphorus QDs (OA-BP QDs) with improved stability and optical properties were successfully synthesized. More importantly, an extraordinary CL emission when OA-BP QDs reacted with SO32- was first observed. In the CL process, OA-BP QDs acted as the catalyst to trigger singlet oxygen (1O2) generation in NaHSO3, and then a chemiluminescence resonance energy transfer (CRET) between (1O2)2* (1O2 dimeric aggregate) and OA-BP QDs was produced. On this basis, a new CL system for directly monitoring SO32- in airborne fine particulate matter (PM2.5) was fabricated. The study opens attractive perspectives of modified metal-free QDs for the practice of CL in monitoring the chemical species in PM2.5.Quantum dots (QDs), especially metal-free QDs with their unique optoelectronic properties, environmental friendliness, and excellent biocompatibility, have opened a new avenue to explore novel chemiluminescence (CL) systems for analytical applications. However, the unknown CL properties, relatively weak emission, and instability of some of them in water (e.g., black phosphorus QDs) often seriously hinder their further practical applications. Chemical modification trends have offered new properties for materials and have been proved to be desirable ways to establish sensing platforms with improved sensitivity and stability. Herein, oleic acid capped black phosphorus QDs (OA-BP QDs) with improved stability and optical properties were successfully synthesized. More importantly, an extraordinary CL emission when OA-BP QDs reacted with SO32- was first observed. In the CL process, OA-BP QDs acted as the catalyst to trigger singlet oxygen (1O2) generation in NaHSO3, and then a chemiluminescence resonance energy transfer (CRET) between (1O2)2* (1O2 dimeric aggregate) and OA-BP QDs was produced. On this basis, a new CL system for directly monitoring SO32- in airborne fine particulate matter (PM2.5) was fabricated. The study opens attractive perspectives of modified metal-free QDs for the practice of CL in monitoring the chemical species in PM2.5.